A Companion to Greek and Roman Sexualities - Hubbard, Thomas K. (Hoboken : John Wiley & Sons Inc., 2014)
"A Companion to Greek and Roman Sexualities presents a comprehensive collection of original essays relating to aspects of gender and sexuality in the classical world. Views the various practices and discursive contexts of sexuality systematically and holistically Discusses Greece and Rome in each chapter, with sensitivity to the continuities and differences between the two classical civilizations Addresses the classical influence on the understanding of later ages and religion Covers artistic and literary genres, various social environments of sexual conduct, and the technical disciplines of medicine, magic, physiognomy, and dream interpretation Features contributions from more than 40 top international scholars "--
"Discusses Greece and Rome in each chapter, with sensitivity to the continuities and differences between the two classical civilizations"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Greek literature -- History and criticism; Latin literature -- History and criticism; Sex -- Greece -- History; Sex -- Rome -- History; Sex in literature; LITERARY CRITICISM / Ancient & Classical; Greek literature; Latin literature; Manners and customs; Sex; Sex in literature; Greece -- Social life and customs; Rome -- Social life and customs; Greece; Rome (Empire); Electronic books; Criticism, interpretation, etc; History